The geometry of the trochlear groove - Iranpour, F.; Merican, A.M.; Dandachli, W.; Amis, A.A.; Cobb, J.P. (Springer, 2010)
Background In the natural and prosthetic knees the position, shape, and orientation of the trochlea groove are three of the key determinants of function and dysfunction, yet the rules governing these three features remain elusive. Questions/Purpose The aim was to define the three-dimensional geometry of the femoral trochlea and its relation to the tibiofemoral joint in terms of angles and distances. Methods Forty CT scans of femurs of healthy patients were analyzed using custom-designed imaging software. After aligning the femur using various axes, the locations and orientations of the groove and the trochlear axis were examined in relation to the conventional axes of the femur. Results The trochlear groove was circular and positioned laterally in relation to the mechanical, anatomic, and transcondylar axes of the femur; it was not aligned with any of these axes. We have defined the trochlear axis as a line joining the centers of two spheres fitted to the trochlear surfaces lateral and medial to the trochlear groove. When viewed after aligning the femur to this new axis, the trochlear groove appeared more linear than when other methods of orientation were used. Conclusions Our study shows the importance of reliable femoral orientation when reporting the shape of the trochlear groove.